An overview of polybrominated diphenyl ethers (PBDEs) in the marine environment - Lee, Hyo Jin; Kim, Gi Beum (Ocean science journal, 2015)
Polybrominated diphenyl ethers (PBDEs), which are used extensively as brominated flame retardants, are found ubiquitously in marine environments worldwide. In this paper, we review all available data on the occurrence and trends of PBDEs in marine environments. PBDE levels in different marine environmental compartments vary from nanograms per gram to micrograms per gram, and differ widely, depending on the exposed species and the collection site. The PBDE congener profiles in biota, which are dominated by the lower brominated congeners, such as BDE-47 and BDE-99, are different from those in sediments, where BDE-209 is dominant. Temporal trends in PBDE levels in sediment cores vary considerably, depending on the region or country studied, with possible correlations with the historic and current use of PBDEs. Low brominated BDE congeners have the potential for bioaccumulation in marine organisms, but BDE- 209 has a very low potential for bioaccumulating within the marine food web. The toxicological effects of PBDEs on marine organisms are largely unknown. However, PBDE isomers may be sufficient to elicit adverse effects in some marine organisms. Here, we discuss naturally occurring brominated diphenyl ethers and recommend further research to improve future monitoring.